Valor alimentar do feno de Tifton 85 (Cynodon sp.) com ou sem suplementação com uréia, caseína ou farinha de mandioca - Reffatti, Mônica Vizzotto (2006)
To evaluate the effect of supplement type on nutritional value of diets based on a low-quality forage, ten Polwarth × Texel lambs (mean LW of 21 ± 3 kg), housed in metabolic cages, fed ad libitum with a grass hay (Cynodon sp.) cut with 90 days of regrowth age, were used in a double 5 x 5 Latin Square experiment. Supplements tested were urea (U), cassava meal (CM), cassava meal plus urea (CMU) or cassava meal plus sodium caseinate (CMCA). A control (H) treatment (no supplement) was also included. Hay and fiber intake, as well as fiber digestibility, rumen microbial protein synthesis and nitrogen (N) retention were the lowest (P<0.05) by lambs supplemented only with cassava meal. Total organic matter (OM), as well as digestible energy intake, rumen microbial protein synthesis and N retention were improved (P<0.05) only by animals supplemented with cassava meal plus either, caseinate or urea. Lambs non-supplemented or supplemented only with cassava meal had very lower (P<0.05) ruminal ammonia concentrations. Sugars concentration was the highest (P<0.05) in lambs supplemented only with cassava meal. Casein treatments elicited the highest (P<0.05) ruminal concentrations of amino acids and peptides. Hay utilization by lambs was not improved by any supplement tested and was markedly depressed as cassava meal was the sole supplement. This effect, however, was not due a decreasing in ruminal pH, given that the mean ruminal pH values were always near 7.0. Increased nutrients supply for lambs fed a low-quality grass hay was dependent on both, energetic and nitrogenous substrates availability. However, none of tested supplements improved the forage use by animals indicating that its utilization is not limited due a lack of substrates for rumen microorganisms. It is probably that others factors, such as those associated with physical, chemical and anatomical characteristics of forage, but not a lack of N, have limited bacterial access and forage degradation into the rumen. Moreover, it is also possible that supplements have affected the particles passage rate through the gastrointestinal tract of lambs. These effects, however, need are considered in further studies